2013
DOI: 10.4028/www.scientific.net/amr.750-752.1385
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Lignin as a Carbonization Agent on the Thermal Degradation and Flame Retardancy of Intumescent Flame Retardant Coating

Abstract: The influence of alkali lignin (AL) as a carbonization agent on the thermal degradation and flame retardancy of intumescent flame retardant (IFR) coating was investigated under air condition, with ammonium polyphosphate (APP) as an acid source, and melamine (MEL) as a blowing agent. Compared with a traditional APP/pentaerythritol (PER) /MEL IFR system, thermogravimetric analysis (TGA) results showed that APP/AL/MEL IFR system could induce the synergistic effect at a much boarder temperature range, and improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Flame retardant coating is an application of lignin coating that is recently getting attention in the nonwoven and textile fields (Reti et al 2009;Jiao and Wu 2013;Łukawski et al 2020). An intumescent flame-retardant (IFR) coating protects the fabrics by forming an intumescent charred layer, and this layer prevents the heat transfer and combustion of nonwoven fabrics (Fu et al 2017;Lopez-Cuesta 2017).…”
Section: Lignin As a Flame Retardant Coatingmentioning
confidence: 99%
“…Flame retardant coating is an application of lignin coating that is recently getting attention in the nonwoven and textile fields (Reti et al 2009;Jiao and Wu 2013;Łukawski et al 2020). An intumescent flame-retardant (IFR) coating protects the fabrics by forming an intumescent charred layer, and this layer prevents the heat transfer and combustion of nonwoven fabrics (Fu et al 2017;Lopez-Cuesta 2017).…”
Section: Lignin As a Flame Retardant Coatingmentioning
confidence: 99%
“…It was observed that alkali lignin provides better fire retardant performance than that of the coating with the same loading of PER as a carbon source. 97…”
Section: Classical Intumescent Additivesmentioning
confidence: 99%
“…In recent years, with the lack of petroleum resources and the enhancement of people’s awareness of environmental protection, biomass carbon sources have gradually emerged [16,17,18]. Therefore, we reported the preparation of flame-retardant microspheres (K-CM/APP) by covering APP with the k-carrageenan (KC) wall.…”
Section: Introductionmentioning
confidence: 99%